2018
DOI: 10.1186/s13287-018-0886-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved GMP compliant approach to manipulate lipoaspirates, to cryopreserve stromal vascular fraction, and to expand adipose stem cells in xeno-free media

Abstract: BackgroundThe stromal vascular fraction (SVF) derived from adipose tissue contains adipose-derived stromal/stem cells (ASC) and can be used for regenerative applications. Thus, a validated protocol for SVF isolation, freezing, and thawing is required to manage product administration. To comply with Good Manufacturing Practice (GMP), fetal bovine serum (FBS), used to expand ASC in vitro, could be replaced by growth factors from platelet concentrates.MethodsThroughout each protocol, GMP-compliant reagents and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 63 publications
1
60
0
1
Order By: Relevance
“…ASC were chosen as model of in vitro proliferating cells: the experimental protocol was approved by the Ethics Committee of the CRO Aviano National Cancer Institute (protocol number: CRO-2016-30) and it complied with the Declaration of Helsinki (2004). Cells were obtained as previously published [ 4 ] from n = 3 separate donors and they were seeded at passage P4 in 96-well plates (BD Biosciences, Bedford, MA; US) at 3000 cells/cm 2 in complete Minimum Essential Medium Eagle - Alpha Modification (Alpha-MEM - Lonza; Basel, Switzerland)) containing 100 IU/ml of Penicillin, 100 microg/ml of Streptomycin (both from Sigma, St. Louis, MO; USA) and 5% (vol/vol)SRGF. After 4-6 hours, adherent cells were washed and medium was replaced with Alpha-MEM containing antibiotics and 5% (vol/vol) A, B, C and D (pools) each in four technical replicate wells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ASC were chosen as model of in vitro proliferating cells: the experimental protocol was approved by the Ethics Committee of the CRO Aviano National Cancer Institute (protocol number: CRO-2016-30) and it complied with the Declaration of Helsinki (2004). Cells were obtained as previously published [ 4 ] from n = 3 separate donors and they were seeded at passage P4 in 96-well plates (BD Biosciences, Bedford, MA; US) at 3000 cells/cm 2 in complete Minimum Essential Medium Eagle - Alpha Modification (Alpha-MEM - Lonza; Basel, Switzerland)) containing 100 IU/ml of Penicillin, 100 microg/ml of Streptomycin (both from Sigma, St. Louis, MO; USA) and 5% (vol/vol)SRGF. After 4-6 hours, adherent cells were washed and medium was replaced with Alpha-MEM containing antibiotics and 5% (vol/vol) A, B, C and D (pools) each in four technical replicate wells.…”
Section: Methodsmentioning
confidence: 99%
“…In a previously published work, we demonstrated that such GMP compliant medium additive can efficiently stimulate stromal cell proliferation in culture [ 3 ]. Moreover, in a recent paper [ 4 ] we demonstrated that SRGF can strongly promote growth of adipose mesenchymal stromal stem cells (ASC) by direct analysis of cell proliferation and evaluating cell morphology. Rapidly dividing mesenchymal stem cells are, in fact, known to be elongated and spindle shaped [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASCs and adipose-derived stem/progenitor cells are thought to have overlapping paracrine and immunosuppressive functions and the bulk of the clinical effects are thought to be caused by the ASCs [Viswanathan et al, 2019]. The reported percentage of adipose-derived stem/progenitor cells in the SVF ranges from < 1%, as determined according to a narrow definition of colony-forming units (CFU-F), whereas ASCs seem to make up more than 20% when defined according to surface markers only [Bourin et al, 2013;Agostini et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different digestion conditions may affect phenotypical and functional characteristics of the isolated cells . Moreover, the procedure is generally considered expensive, because clinical grade products must be used to avoid xenogenic contamination . More importantly, collagenase digestion to isolate SVF falls outside the “minimal manipulation” guidelines set by regulatory agencies since the procedure alters substantially the original characteristic of the adipose tissue.…”
Section: Introductionmentioning
confidence: 99%